The implementation of progressive mathematization model as a mean to enhance understanding and communication ability of junior high school students - Klara Iswara Sukmawati (Jurnal Riset Pendidikan Matematika, 2018)
The study was based on the importance of students’ mathematical understanding and communication ability. Students need some efforts in attaining mathematical understanding and communication ability. As a result, the researcher sensed that it should be designed A Progressive Mathematization Model in order to enhance the mathematical understanding and communication ability of the students especially the junior high school ones. Then, in conducting the study the main purpose was to analyze the enhancement of mathematical understanding and communication ability of the students. The study was a quantitative research. The population in this study was the seventh-grade students of SMPN 1 Pagedangan and the sample in this study consisted of two groups that had been selected by applying a purposive sampling. The researcher utilizing four test instruments of mathematical understanding and communication ability within the study. The data that had been gathered would be analysed by means of independent t-test. The findings of the study showed that the enhancement of mathematical understanding and communication ability of the students through a progressive mathematization model had been better than the enhancement of mathematical understanding and communication ability of the students using the conventional learning.